Hydrodynamic flow and benthic boundary layer interactions shape the microbial community in Milos shallow water hydrothermal vents - Silva, Ana Clara Pelliciari; Migliaccio, Flavia; Barosa, Bernardo; Gallucci, Luigi; Yücel, Mustafa; Foustoukos, Dionysis; Le Bris, Nadine; Bartlett, Stuart J.; D’Alessandro, Valerio; Vetriani, Costantino; Giovannelli, Donato (Frontiers in Microbiology, 2025)
In shallow-water hydrothermal vents, the dynamic interface between the discharged reduced hydrothermal fluids and the oxidized seawater allows the establishment of gradients capable of supporting diverse and complex microbial mats. Due to their shallow depths and proximity to land masses, shallow vents are heavily influenced by dynamic forcing, tidal fluctuations, and episodic events (e.g., storms, tides, etc.). Although several studies have investigated the microbial communities inhabiting shallow vents in the last decades, less is known about how microbial communities respond to episodic events and how the complex interplay of physical and chemical drivers shapes the establishment and structure of microbial biofilms in these systems. Here we present data combining the taxonomic and functional diversity of the white microbial mats commonly found in sulfide rich shallow-water hydrothermal vents in Paleochori Bay (Milos Island, Greece), using a combined approach of 16S rRNA transcript amplicon sequencing (from RNA) and shotgun metagenomic sequencing (from which 16S rRNA genes were retrieved). We show that the white microbial mats of Milos shallow-water hydrothermal vents are dominated by Epsilonproteobacteria, now classified as Campylobacterota, with metabolic functions associated with chemolithoautotrophic lifestyles and exposed to a diverse array of viral communities. Taxonomic names follow the classification available at the time of analysis (2012). We explore how dynamic forcing and storm events influence microbial community restructuring and turn-over, and provide evidence that dynamic interactions with the benthic boundary layer play a key role in controlling the spatial distribution of taxa. Overall, our results show diverse processes through which geodynamic events influence microbial taxonomic and functional diversity.